2017
DOI: 10.1016/j.rmcr.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of pulmonary injury after nitrogen oxide exposure with corticosteroid therapy: A case report and review of the literature

Abstract: Nitrogen oxides are representative chemicals of occupational and environmental exposure, which can lead to fatal pulmonary injury. These oxides are also known to cause delayed occurrence of bronchiolitis obliterans (BO). Herein, we report a case of nitrogen oxide-induced lung injury. A 50-year-old man developed pulmonary edema after nitric acid exposure. Hypoxemia and respiratory failure were immediately improved after introduction of corticosteroid pulse therapy with supplemental oxygen. This was followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The patient described by Murphy et al received both NO and corticosteroids, however, did not survive. There is no specific literature that supports efficacy of NO in nitric acid induced pulmonary edema and acute respiratory distress syndrome; however, there are numerous case reports that suggest efficacy of corticosteroid usage in the treatment of patients with HNO 3 induced lung injury [3, 10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient described by Murphy et al received both NO and corticosteroids, however, did not survive. There is no specific literature that supports efficacy of NO in nitric acid induced pulmonary edema and acute respiratory distress syndrome; however, there are numerous case reports that suggest efficacy of corticosteroid usage in the treatment of patients with HNO 3 induced lung injury [3, 10].…”
Section: Discussionmentioning
confidence: 99%
“…In their case they note that the patient did not begin to show signs of improvement until time of administration of corticosteroids. In their manuscript they further review prior case reports of HNO 3 exposure and treatment, noting most received corticosteroid therapy [10]. Further they note that, in one case report by Lee et al (2013), a patient survived after receiving corticosteroid therapy for only a short 5-day course; however, the patient developed bronchiolitis obliterans, a possible sequela of nitric acid lung injury 1 month later.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the above reports showed that such high dosages of NO were well-tolerated in tested patients, they may bring along toxic side effects to others. For instance, after high dosages (≥80 ppm) of NO inhalation, methemoglobinemia can be observed, and the high concentrations of toxic nitrogen dioxide generated from spontaneous oxidation result in direct injury to the alveolar epithelial cells and may even cause pulmonary oedema (Davidson et al 1998 ; Kido et al 2017 ). In addition, the toxic reactive nitrogen intermediates such as peroxynitrite generated under conditions of high-NO flux may induce structural alterations in DNA and cell damage, interfere with the activity of lung surfactants and increase surface tension (Hallman and Bry 1996 ).…”
Section: No Delivery In Vivomentioning
confidence: 99%
“…The symptomatic treatment of lung inhalation injury from HNO 3 has been shown to be largely supportive, and it remains unstandardized ( 63 ). Kido et al ( 65 ) reported a case of HNO3-induced pulmonary injury with improvement after corticosteroid administration. Meaden et al ( 63 ) reported a case of pulmonary edema occurring after HNO 3 inhalation, which improved after the bronchodilator treatment.…”
Section: Ecmo For Acute Toxic Inhalationmentioning
confidence: 99%